2019
DOI: 10.1177/0954405419862479
|View full text |Cite
|
Sign up to set email alerts
|

Tool wear and resulting surface finish during micro slot milling of polycarbonates using uncoated and coated carbide tools

Abstract: A growing application of polycarbonates is in the microfluidic disks and DNA detection devices, where surface finish of the micro-channels plays an important role. This study intends to investigate the tool wear and surface finish generated during micro slot milling of polycarbonate using uncoated, TiN-coated, and TiAlN-coated tungsten carbide tools. The effects of tool coating and the machining parameters on the possible reduction of tool wear and improvement of surface finish were investigated. It was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…35 Machining of hard materials, as in the case of WHAs, involves discontinuous chip formation, which possibly leads to formation of abrasive or adhesive wear on the flank surface with built-up edge (BUE). 68 Chen et al 9 evaluated abrasiveness index and observed diffusion, chemical, abrasive and micro-chipping as the major cause for rapid crater wear, while dry machining high chromium cast iron using polycrystalline cubic boron nitride (PCBN) inserts. Similarly, Kagnaya et al 10 observed severe wear near chip/tool contact due to abrasion and pullout phenomena during dry machining on AISI 1045 steel using tungsten carbide (WC)-6Co uncoated carbide tools and Zhang et al also evaluated tool failure for TC21 alloy under dry machining using coated carbide tools, and from scanning electron microscopic (SEM) analysis, it was found that adhesion and chipping were significant factors responsible for tool failure.…”
Section: Introductionmentioning
confidence: 99%
“…35 Machining of hard materials, as in the case of WHAs, involves discontinuous chip formation, which possibly leads to formation of abrasive or adhesive wear on the flank surface with built-up edge (BUE). 68 Chen et al 9 evaluated abrasiveness index and observed diffusion, chemical, abrasive and micro-chipping as the major cause for rapid crater wear, while dry machining high chromium cast iron using polycrystalline cubic boron nitride (PCBN) inserts. Similarly, Kagnaya et al 10 observed severe wear near chip/tool contact due to abrasion and pullout phenomena during dry machining on AISI 1045 steel using tungsten carbide (WC)-6Co uncoated carbide tools and Zhang et al also evaluated tool failure for TC21 alloy under dry machining using coated carbide tools, and from scanning electron microscopic (SEM) analysis, it was found that adhesion and chipping were significant factors responsible for tool failure.…”
Section: Introductionmentioning
confidence: 99%
“…where g is a positive constant. l i , b, and c are the parameters to be determined, respectively, which are obtained by equations (17) and (18) in the matrix form…”
Section: Radial Basis Function Modelmentioning
confidence: 99%
“…Pham et al 17 stated that the tool-chip contact length, the workpiece vibration, and the surface roughness were increased with F o r P e e r R e v i e w 4 increasing cutting depth and feed rate for the dry milling of A6061 aluminum alloy. Jahan et al 18 concluded that the mid-level of the feed and depth of cut could be used to decrease the tool wear and surface roughness in the milling of polycarbonates. Mia and Dhar 19 emphasized that specific cutting energy was influenced favorably by the increase in cutting speed.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, past research highlights the effect of machining variables on tool-life. 20,21 Tamizharasan et al 22 examined the effect of turning variables on PCBN cutting-tool inserts; they reported that speed has maximum influence on the tool life, while DOC has a minimal effect. Nur et al 23 studied the turning parameters impact in machining AISI 316L alloy, their findings exhibited that speed and feed are inversely proportional to the tool life.…”
Section: Introductionmentioning
confidence: 99%